Heuristic and meta dendral systems: A review - AlFarsi G.; Tawafak R.M.; Malik S.I.; Alsideiri A.; Mathew R. (Institute of Electrical and Electronics Engineers Inc., 2023)
Engines; Learning systems; Chemical science; Complex problems; Dendral; Heuristic; Human knowledge; Intelligence expert system; Performance; Stepping-stones; System learning; Expert systems